Bistable Wave Fronts in Integrodifference Equations - Shuxia Pan; Ping-An Zhang (Abstract and Applied Analysis)
This paper is concerned with the bistable wave fronts of integrodifference equations. The existence, uniqueness, and asymptotic stability of bistable wave fronts for such an equation are proved by the squeezing technique based on comparison principle.